MnxZn1-xFe2O4 coated with β-Bi2O3 and β-MnO2 as a highly efficient and magnetically recyclable photocatalyst for water treatment. (11th May 2020) - Wu, Tingzeng; Wang, Weifang; Xu, Longjun; Liu, Chenglun; Xiang, Wu; Lu, Yuan; Wang, Hailong; Feng, Qi; Chen, Hongchong
ABSTRACT: Magnetic photocatalyst β-Bi2 O3 /β-MnO2 /Mn x Zn1- x Fe2 O4 (BM/MZF) was successfully synthesised using dip-calcination method. The structure and properties of as-prepared samples were characterised by XRD, SEM, FT-IR, UV-DRS and VSM. The peaks of β-Bi2 O3 and β-MnO2 without an obvious change in the XRD pattern of BM/MZF confirmed that their morphology and phase stayed stable during the process of preparation. BM/MZF with a structure of bulked Mn x Zn1- x Fe2 O4 coated with spherical and flaky β-Bi2 O3 and spherical β-MnO2 possesses good optional and magnetic abilities. The band gap of BM/MZF (2.34 eV) was less than that of β-Bi2 O3 (2.48 eV) or β-Bi2 O3 /Mn x Zn1- x Fe2 O4 (2.43 eV). Under visible light irradiation, the photodegradation rate of RhB using BM/MZF was 98.9% in 1.75 h, which was higher than that using β-Bi2 O3 (48%) or β-Bi2 O3 /Mn x Zn1- x Fe2 O4 (65%), and the photodegradation rate was still 95.7% after five cycles. The saturation magnetisation (Ms) of BM/MZF was 6.95 emu/g, and the average recovery rate was 87%.